Pengembangan Modul Pembelajaran Individual untuk Meningkatkan Kualitas dan Hasil Pembelajaran dalam Matakuliah Pengetahuan Bahan - Eddy Sutadji (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Developing an Individualized Learning Module to Improve the Quality of Learning Processes and Outcomes. The study was intended to develop an effective learning module, which is based on procedural-content-learning principles, for a course on material knowledge. The module was expected to improve the quality of learning processes and outcomes. Equipped with other components such as manual, material diagram, specific learning objectives, contents, pictures, exercises, and summaries, the module becomes easy to learn and understand. The research findings suggest that the module provides contribution to the learning outcomes when applied in procedural-content learning.